A comparative study of levels of vitamin B12 in patients of type 2 diabetes mellitus on metformin and not on metformin at tertiary care center - Agarwal, Priti; Mital, Pradeep; Meena, Vinay Kumar; Mital, Premlata; Nawal, C. L.; Goyal, Laxmi Kant (International Journal of Advances in Medicine, 2016)
Background: Type 2 diabetes mellitus is associated with vitamin B12 deficiency which is further increased in patients who are on metformin therapy. The objective of this study is to determine the frequency of vitamin B12 deficiency among Indian patients with type 2 diabetes mellitus on metformin therapy compared to those who are not on metformin. Methods: The study was a hospital based, case control type of analytical study conducted in SMS Medical College & Hospital, Jaipur during a period of 1 year. The study group has 50 patients with a diagnosis of T2DM and a prescription history of metformin for ≥18 months and control group has 50 patients with diagnosis of T2DM and no history of metformin use in the past five years. The following data was recorded for each patient: age, sex, weight, height, body mass index (BMI), years with diabetes, total daily dose of and years on metformin. Serum vitamin B12 was measured using an immunoassay method. Data were statistically analyzed. Results: Mean serum vitamin B12 levels in the study group was 431.84±265.76 and in control was 744.76±271.927 and the difference was statistically significant. Mean serum vitamin B12 levels in vegetarians (547.27±303.011) were significantly lower than in non-vegetarian (699.22±307.992) (p value 0.029). A significant negative correlation existed between the S. vitamin B12 and duration of diabetes (r= -0.445) by using Pearson’s correlation coefficient in study group. Conclusions: Metformin is significantly associated with decrease in vitamin B12. So we recommend that vitamin B12 should be measured prior to initiation of metformin therapy and later annually in patients of type 2 diabetes mellitus who are on metformin therapy for long duration (≥3-4 years) or in higher doses (≥2gm/day).